(untitled) (Teacher’s World: Journal of Education and Research, 2024)
The inaugural issue of the 50th volume of Teacher’s World: Journal of Education and Research features a collection of eight scholarly articles that explore the challenges and opportunities within Bangladesh’s education sector. These articles address various facets of education, such as the struggles of marginalized communities, digital learning, and pedagogical advancements. The thematic synthesis of these articles offers significant insights into the diverse dimensions of education, encompassing issues from the obstacles faced by marginalized groups to the impacts of digital learning and innovative teaching methods. Bangladesh confronts numerous challenges in promoting inclusive and practical education due to its diverse socio-economic landscape. Economic inequalities, gender disparities, infrastructure deficiencies, and technological gaps impede students’ access to quality education. The analysis of the selected articles highlights that government initiatives aimed at equitable resource allocation and inclusive education can bridge existing gaps. Strengthening community engagement can address local educational needs, ensuring accessibility and tailored support. Additionally, innovative teaching methods, such as the flipped classroom model and experiential learning, can enhance student engagement and learning outcomes. The role of public-private partnerships in mobilizing resources, expertise, and technology is crucial for improving educational infrastructure and quality. Collaborations between the government, private sector, and NGOs can create comprehensive solutions to educational challenges. Addressing these challenges and leveraging opportunities requires a multifaceted approach involving policy reform, community engagement, innovative teaching methods, and strategic partnerships. By fostering inclusive and practical education, Bangladesh can pave the way for a brighter and more equitable future for its students. Furthermore, participation in global educational initiatives and networks can introduce new perspectives, resources, and best practices, enriching the local education system and fostering continuous improvement. Teacher’s World: Journal of Education and Res arch, 50(1): 1-5